INCLUSIVE NON-POSITIVISM - Alexy, Robert (Espaço Jurídico Journal of Law [EJJL], 2015)
On the basis of the distinction between two forms of positivism and three forms of non-positivism, I argue that only one of these five concepts of law is defensible: inclusive non-positivism. The basis of my argument is the correctness thesis, which says that law necessarily makes a claim to correctness. The doctrine of correctness implies the dual nature thesis, which says that law comprises a real or authoritative dimension as well as an ideal or critical dimension. The dual nature of law is the basis of the Radbruch formula. It says, in its shortest form, that extreme injustice is not law. Keywords: Inclusive non-positivism. Correctness. Dual nature of law. Injustice.